Effects of IGF-1 mediated enrichment environment on visual cortex plasticity in adult amblyopic mice - Yu-Lin Luo (Guoji Yanke Zazhi, 2020)
AIM: To investigate the effect and possible mechanism of enriched environment on regulating the plasticity of visual cortex in adult monocular deprivation amblyopia mice. METHODS: In this experimental study, a total of 72 Kunming mice were randomly divided into control group(Nor), monocular deprivation+ standard environment group(MD+SE), monocular deprivation + enriched environment group(MD+EE)and monocular deprivation+ fluoxetine group(MD+FLX). MD model of mice were established at postpartum 21d, and then fed the mice under SE or EE for 4wk. For the mice in MD+FLX group, they were fed by water with fluoxetine. The visual acuity and flash visual evoked potential of mice in each group were detected. Ultrastructral modifications of synaptic junctions in each group were detected using the electronic microscope. We also applied the molecular biology to study the role of enriched environment in visual cortex of adult amblyopic mice whether through regulating the expression of IGF-1, IGF-1R and IGFBP5. RESULTS: 1)Visual acuity examination: the successful rate of forepaw-reaching reflex in MD+SE group mice is lower than that in Nor group(P<0.001). Compared to MD+SE group, the successful rate of forepaw-reaching reflex improved in MD+EE group(P<0.001)and MD+FLX group(P<0.001). The difference is not significant between the MD+EE group and MD+FLX group(P=0.816); 2)Flash-visual evoked potential examination: compare to the Nor group, the P2 latency was prolonged(P<0.01), and the P2 amplitude was decreased(P<0.01)of flash-visual evoked potential(F-VEP)in the deprived eye in MD+SE group mice; After raring in enriched environment, the P2 latency was shortened(P=0.003)and P2 amplitude was increased(P=0.000)in the deprivated eye detected with F-VEP, which is not significant in P2 latency and amplitude when compare to MD+FLX group(P>0.05); 3)The structural modifications of synaptic junctions examined by electromicrographs: Compare to the Nor group, the synaptic clefts increased(P<0.01), the synaptic active zone shortened(P<0.01), and the thickness of PSD decreased(P<0.01)in MD+SE group mice. After raring in enriched environment, the synaptic clefts decreased(P=0.0035), the synaptic active zone prolonged(P=0.000)and the thickness of PSD increased(P=0.000)in the visual cortex contralateral to the deprived eye, which is not significant in all of the structural parameters of the synaptic junction in visual cortex when compare to MD+FLX group(P>0.05); 4)IGF-1, IGF-1R and IGFBP5 expression detected by Western-blot: Compare to the Nor group, the IGF-1 and IGF-1R expression in visual cortex contralateral to deprivated eye are both down-regulated in MD+SE group(P<0.01; P<0.01). After raring in enriched environment, the expression of IGF-1 and IGF-1R in MD+EE group was significantly higher than that in MD+SE group(P=0.016; P=0.041), but still lower than that in Nor group(P=0.001; P=0.001). The different expression of IGFBP5 in each group is not significant(P>0.05). CONCLUSION: Environmental enrichment can improve the visual function through reactivating the plasticity of monocular deprivation amblyopia mice. The mechanism is presumed to be related to the expression of IGF-1 and IGF-1R.